Community-based Stem Ecosystem in Indonesian Muslim Communities - Indri Ajeng Setyoningrum; Tri Handoko (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to formulate a model of a community-based STEM innovation ecosystem within the context of non-formal education in Indonesian Muslim communities. The background of this review is rooted in the limited access to relevant STEM education for Muslim communities, particularly in rural and peri-urban areas, alongside the substantial potential of Islamic non-formal educational institutions-such as Islamic boarding schools (pesantren), Qur'anic learning centers (TPA), and Islamic study groups (majelis taklim)-to serve as venues for contextual learning. The research employed a literature review of over 50 sources-including peer-reviewed journals, academic books, policy documents, and research reports-analyzed thematically and critically. The analysis process involved thematic coding, conceptual synthesis, critical evaluation, and the construction of a conceptual model. Findings indicate that an effective STEM innovation ecosystem requires six key components: (1) community-based learning environments, (2) local actors serving as facilitators, (3) contextual curricula integrated with Islamic values, (4) project-based learning methods, (5) accessible low-tech support, and (6) strategic partnerships with external stakeholders. This model is holistic and participatory, aligning with the social, cultural, and spiritual characteristics of Muslim communities. The findings provide a conceptual contribution to value-driven, locally grounded non-formal education innovations and offer insights for more responsive policy and practical frameworks. The study recommends capacity-building for facilitators, adaptive curriculum development, and strengthened multi-sectoral collaboration as strategic measures for the sustainable implementation of the model.